CLEANING NATURAL AND ASSOCIATED GASES FROM SULFUR COMPOUNDS - ISMADIYOROV, AKMALJON; URINBOEVA, MARIFATOY (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
To develop innovative methods of cleaning natural and associated gas from sulfur compounds. Studying the positive and negative aspects of using physical, chemical and combined methods in cleaning natural and associated gases and developing new innovative methods. Today, physical, chemical, combined methods are used to purify gases from sulfur compounds. Sorbents are imported from abroad. When sorbents are developed in local conditions, their price can be 3-5 times cheaper.